Analisis Pengaruh E-Costumer Relationship Management Terhadap E-Satisfaction dan E-Loyalty Pengguna Access by KAI - Indah Indri Arti; Muhamad Awiet Wiedanto Prasetyo (Telkom University, 2026)
The rapid development of information and communication technology has significantly transformed consumer behavior, particularly in the way people access and purchase products and services. The increasing adoption of digital platforms has encouraged consumers to shift from conventional offline transactions to online-based services, including the purchase of railway transportation tickets. In Indonesia, PT Kereta Api Indonesia (KAI) has responded to this trend by developing the Access by KAI mobile application, which provides various services such as ticket reservations, payment facilities, travel information, and customer support. However, the relatively low number of user reviews on the Google Play Store and Apple App Store compared to the total number of application downloads indicates the existence of several issues related to customer engagement, satisfaction, and loyalty. These conditions highlight the importance of evaluating the effectiveness of Electronic Customer Relationship Management (E-CRM) in maintaining positive relationships with customers. This study aims to analyze the influence of E-CRM on E-Satisfaction and E-Loyalty among users of the Access by KAI mobile application on railway routes within the Java region. The research employed a quantitative approach using a non-probability sampling method with a purposive sampling technique. A total of 400 respondents who had experience using the Access by KAI application participated in the study. Data were collected through questionnaires and analyzed to examine the relationships among the research variables. The findings reveal that E-CRM has a positive and significant effect on E-Satisfaction. In addition, E-CRM also positively influences E-Loyalty. Further analysis demonstrates that E-Satisfaction plays an important mediating role in the relationship between E-CRM and E-Loyalty. Although the direct effect of E-CRM on E-Loyalty is relatively limited, customer satisfaction significantly strengthens customer loyalty toward the application and its services. These results indicate that effective implementation of E-CRM strategies can enhance customer satisfaction, which in turn contributes to stronger customer loyalty. Therefore, organizations should focus not only on improving customer relationship management systems but also on continuously enhancing customer satisfaction to ensure long-term customer retention and loyalty in the digital service environment.